The Dynamic Impacts of Monetary Policy: An Exercise in Tentative Identification - Gordon, David B.; Leeper, Eric M. (Journal of Political Economy, 1994)
It is currently popular to identify monetary policy shocks with innovations in some measure of reserves or in the federal funds rate. These assumptions about the interest elasticity of the supply of or demand for reserves imply monetary policy shocks that produce dynamic responses of macroeconomic variables that are anomalous relative to traditional monetary analyses. This paper tentatively identifies supply and demand shocks in the markets for reserves and M2 for the 1980s and contrasts them with results for the 1970s. In the later period, identified monetary policy shocks have dynamic impacts that are fully consistent with traditional analyses.